Abundance of MMPs and Cysteine Cathepsins in Caries-affected Dentin. (March 2014) - Vidal, C.M.P.; Tjäderhane, L.; Scaffa, P.M.; Tersariol, I.L.; Pashley, D.; Nader, H.B.; Nascimento, F.D.; Carrilho, M.R.
Degradation of dentin matrix components within caries dentin has been correlated with the activity of host-derived proteases, such as matrix metalloproteases (MMPs) and cysteine cathepsins (CTs). Since this relationship has not been fully established, we hypothesized that the abundance of MMPs and CTs in caries-affected dentin must be higher than in intact dentin. To test this premise, we obtained 5 slices (200 µm) from 5 intact teeth and from 5 caries-affected teeth (1 slice/tooth) and individually incubated them with primary antibodies for CT-B, CT-K, MMP-2, or MMP-9. Negative controls were incubated with pre-immune serum. Specimens were washed and re-incubated with the respective fluorescent secondary antibody. Collagen identification, attained by the autofluorescence capture technique, and protease localization were evaluated by multi-photon confocal microscopy. The images were analyzed with ZEN software, which also quantitatively measured the percentages of collagen and protease distribution in dentin compartments. The abundance of the test enzymes was markedly higher in caries-affected than in intact dentin. CT-B exhibited the highest percentage of co-localization with collagen, followed by MMP-9, MMP-2, and CT-K. The high expression of CTs and MMPs in caries-affected teeth indicates that those host-derived enzymes are intensely involved with caries progression.